Adsorption and dissolution behaviors of CO2 and n-alkane mixtures in shale: Effects of the alkane type, shale properties and temperature. (1st October 2019) - Zhu, Chaofan; Qin, Xuejie; Li, Yajun; Gong, Houjian; Li, Zijin; Xu, Long; Dong, Mingzhe
Abstract: The adsorbed and dissolved oil in the shale reservoirs can be produced during CO2 injection. However, the effects of different factors on the adsorption and dissolution behaviors of CO2 and oil mixtures in the shale were unclear, such as the oil composition, shale properties and temperature. In this study, a series of adsorption and dissolution tests of CO2 and different n-alkane mixtures in organic-rich shales were performed under different condition. The effects of the alkane type, shale properties and temperature on the adsorption and dissolution amount of mixtures and the replace ability of CO2 to n-alkane were discussed, respectively. The results indicate that the dissolution amount was decreased with the chain length of alkane and increased with TOC and temperature. The adsorption amount of the mixtures in shale was low and only account for 3–16% of total adsorption and dissolution amount, which mainly depended on the specific surface area of the shale samples. Additionally, the replace ability of CO2 to dissolved n-alkane was decreased with the chain length of alkane and temperature. However, there are no obvious rules between the replace ability with TOC of shale. This study can provide useful information for EOR of shale oil reservoirs by CO2 injection and the geological storage of CO2 in shale oil reservoir.